Pengaruh Gaya Belajar Terhadap Motivasi Belajar Peserta Didik Kelas III SD Negeri 2 Latihan SPG Ambon - Tarpono, Wasti; Ritiauw, Samuel Patra; Ritiauw, Leonid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of learning styles on learning motivation of third grade students of SD Negeri 2 Latihan SPG Ambon. The background of this research is based on the diversity of learning styles of students (visual, auditorial, and kinesthetic) that have not been fully accommodated in learning, as well as the low learning motivation experienced by some students. This study uses a quantitative approach with a causal associative research type. The sample in this study were all third grade students as many as 36 people, who were selected using simple random sampling technique. Data were collected through a learning style questionnaire and a learning motivation questionnaire before and after treatment, and supported by observation and documentation. Based on the results of the study showed a significant effect of learning style on learning motivation (sig. 0.000 <0.05). The average motivation increased after learning adapted to visual, auditorial, and kinesthetic learning styles